PROFIL PENGUASAAN KONSEP FISIKA MAHASISWA DIII TEKNIK KIMIA POLITEKNIK NEGERI BANDUNG MELALUI PEMBELAJARAN DIBeK&P2D - I Gede Rasagama (Universitas Tadulako, 2021)
This study aims to determine the profile of mastery of physics concepts for Chemical Engineering Diploma III students at the Bandung State Polytechnic (POLBAN) because of the DIBeK&P2D learning model. The research subjects were DIII students of Chemical Engineering POLBAN. The study was carried out using a quasi-experimental method and a pre-test-post-test design for the control group. The results showed the highest mastery of concepts because the research learning model occurred on the topic of work-energy, followed by Boyle's law, AC power factor, fluid, mechanical heat tare, Joule's law, power in the resistor circuit, and the lowest occurred in the introduction. Because of the conventional learning model, the highest mastery of concepts occurs in Boyle's law, followed by energy work, fluid, AC power factor, power in resistor circuits, mechanical heat tare, preliminary and lowest occurs in Joule's law. Mastery of physics concepts because the research learning model is higher than conventional learning models. Conceptual mastery on learning topics is strongly influenced by the level of relevance and suitability between the characteristics of the topics as learning materials and the characteristics of the learning methods used, including evaluation content to measure the increase in students' mastery of concepts as learning products.